Risk factors and outcome of placenta previa: accrete in a tertiary health care center of Punjab, India - Pal, Davinder; Bhagat, Nisha; Arora, Ritu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The aim of this study was to identify and evaluate risk factors associated with placenta accrete (PA) and its clinical outcome. Methods: A descriptive, case control study was conducted in department of obstetrics and gynecology, GMC Amritsar in which authors retrospectively reviewed data of 180 patients of placenta previa (PP) over 5 years, categorized as PA (cases; n=23) or no PA (control; n=157). Furthermore, these groups were compared as to maternal demographics, intrapartum and postpartum complications and neonatal outcomes. Stepwise logistic regression analysis was done to evaluate the extent to which exposure variable contributed to the incidence of PA including advanced maternal age (AMA), parity, location of placenta and previous caesarian section (CS). Primary aim was to identify and quantify the various risk factors of PA and secondary aim measured incidences of PP, PA and fetomaternal outcome. Results: The cumulative incidence of PA over 5 years was 2.98 per 1000 deliveries. Accrete rate increased with number of CSs at 4.76% in patients with no previous CS versus 45.94% in ≥1 CS (p < 0.003). Anterior PP (AOR 10.128 CI 2.406 -42.632; p <0.001) and number of previous CSs (AOR 36.405, 95% CI 2.743 -483.24, p =0.006) were significant risk factors for PA. AMA (OR >30 years: 4.326 95% CI 0.724 -25.856; p =0.108), parity (AOR 1 vs 0: 2.526 95% CI 0.242-26.41; p=0.439), prior uterine curettage (AOR ≥1 vs 0: 11.143 95% CI 0.522-9.726; p=0.278) although had association with PA but was not statistical significant. Caesarian hysterectomy was done in 95.65% patients of PA while only 1 patient of PP required hysterectomy (p<0.001). Neonatal outcome was similar in both groups. Conclusions: Prior caesarian and anterior PP emerged out as significant predictors of PA. Other risk factors like AMA, multiparous, history of prior uterine curettage, central PP have incremental risk of having PA and such patients should be managed diligently to lower feto-maternal morbidities and mortalities.